On the roles of stress-triaxiality and strain-rate on the deformation behavior of AZ31 magnesium alloys. Issue 2 (1st February 2018) - Kale, C.; Rajagopalan, M.; Turnage, S.; Hornbuckle, B.; Darling, K.; Mathaudhu, S. N.; Solanki, K. N.
ABSTRACT: The presence of complex states-of-stress and strain-rates directly influence the dominant deformation mechanisms operating in a given material under load. Mg alloys have shown limited ambient temperature formability due to the paucity of active slip-mechanisms, however, studies have focused on quasi-static strain-rates and/or simple loading conditions (primarily uniaxial or biaxial). For the first time, the influence of strain-rate and stress-triaxiality is utilized to unravel the active deformation mechanisms operating along the rolling, transverse- and normal-directions in wrought AZ31-alloy. It is discovered that the activation of various twin-mechanisms in the presence of multiaxial loading is governed by the energetics of the applied strain-rates. IMPACT STATEMENT It is shown for the first time that the higher deformation energy associated with dynamic strain-rates, coupled with high-triaxiality, promotes detwinning and texture evolution in HCP alloys with high c/a ratio. GRAPHICAL ABSTRACT: